Comparison of different buckling-restrained brace (BRB) configurations for the structural upgrading of an existing building in UP Diliman - Matanguihan, Daniel C.
Many innovative technologies are coming up for the retrofitting and structural upgrading of existing structures to satisfy the latest seismic code requirements in the country. In this research, buckling-restrained brace (BRB) is the latest innovation chosen to be the lateral resisting element in structurally upgrading and stiffening an existing building in University of the Philippines Diliman. Using two different configurations of buckling-restrained braces, this paper also aims to find the more efficient set-up in lessening the structural drift of structures when subjected to earthquake loads. With ETABS as modeling software, column PMM ratios and percent reduction in point drifts from each bracing configuration are compared. The inverted V was proven to be the more effective bracing configuration compared with V although there is no significant difference in percent reduction of point drifts. This paper is limited to the use of buckling-restrained brace as the lateral bracing element on an existing reinforced concrete building and further studies can also be done using other global innovations.